Pengaruh Pembelajaran Outing Class Terhadap Hasil Belajar Dan Motivasi Belajar Siswa Kelas IV SDS IT Rabbani - Satriani DH; Rukayah Rukayah; Aulia Nur Chasanah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This research is a quantitative research with a quasi-experimental design. The population in this study was the fourth grade students of SDS IT Rabbani, Tanete Riattang District, Bone Regency, totaling 88 students. The sampling technique used is simple random sampling technique. The instruments used are tests and questionnaires. Data analysis techniques are descriptive analysis and inferential analysis using the Independent Sample T-Test. The results obtained in this study are that there are differences in student learning outcomes and motivation between the experimental class and the control class. Also, there is a significant influence using outing class learning on student learning outcomes and motivation. The conclusion of this study is that there is an effect of outing class learning on learning outcomes and learning motivation of fourth grade students at SDS IT Rabbani, Tanete Riattang District, Bone Regency, as evidenced by the results of the Independent Sample T-test with analysis of learning outcomes obtained t count (7,879) > t table (2,015 ) and analysis of learning motivation obtained t count (5,965) > t table (2,015).